Uniticket: A Third Party Universal E-Ticket System Based on Mobile Phone - Hu, Linli; Wang, Yuhao; Li, Dong (Scientific Research Publishing, 2011)
Prepaid energy meters have been widely adopted by utilities in different countries across the world as an innovative solution to the problem of affordability and consumption management. However, the present smart card based systems have some inherent problems like added cost, low availability and lack of security. In the future Smart Grid paradigm, use of smart meters can completely overhaul these prepaid systems by introducing centralized accounting, monitoring and credit-control functions using state-of-the-art telecommunication technologies like WiMAX. In this paper we propose a prepaid smart metering scheme for Smart Grid application based on centralized authentication and charging using the WiMAX prepaid accounting model. We then discuss its specific application to Demand Response and Roaming of Electrical Vehicles.
Keywords: Smart Metering; WiMAX; Smart Grid; Demand Response; Electric Vehicles